2008
DOI: 10.4046/trd.2008.64.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Malignant Pleural Effusion by using Aberrant Methylation of p16 and RARB2

Abstract: Background: A diagnosis of malignant pleural effusion is clinically important, as the prognosis of lung cancer patients with malignant pleural effusion is poor. The diagnosis will be difficult if a cytological test is negative. This study was performed to investigate whether the detection of hypermethylation of the p16 (CDKN2A) and retinoic acid receptor b2 (RARB2) genes in pleural fluid is useful for a diagnosis of malignant pleural effusion. Methods: Pleural effusion was collected from 43 patients and was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The database search yielded 3732 studies for screening with 181 potential studies identified for analysis. After full-text analysis, a total of 36 studies met inclusion criteria 2 3 7–40. A summary of the literature search is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The database search yielded 3732 studies for screening with 181 potential studies identified for analysis. After full-text analysis, a total of 36 studies met inclusion criteria 2 3 7–40. A summary of the literature search is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%